Pengaruh Digital Instagram Marketing terhadap Minat Beli Konsumen Akan Jasa Menginap - Daris Prawira; Ratih Tresnati; Dede R Oktini (UNISBA Press, 2022)
Abstract. This research aims to determine how Instagram Digital Marketing effected Sari Ater Hotel & Resort, Kabupaten of Subang, in terms of the Consumer Purchase Interest. Using a survey method with non-probability sampling as the technique of this study. This research is classified as a quantitative verification type. The respondents in this research were Sari Ater Hotel & Resort, Kabupaten of Subang, consumers. The sample is taken by 100 respondents, in total. The method of analysis data that been used is correlation coefficient analysis which aims to determine the magnitude of Instagram Digital Marketing effect as an independent variabel with Consumer Buying Interest as the dependent variabel. The result of this research indicate that Instagram Digital Marketing has a significant effect in Consumer Buying Interest, with the correlation coefficient showing that there is a very strong relationship between those two variable which is Instagram Digital Marketing and Consumer Buying Interest. The determinant coefficient shows that Instagram Digital Marketing affect Consumer Purchase Interest for services to stay at Sari Ater Hotel & Resort, Kabupaten of Subang. Abstrak. Pengaruh Digital Instagram Marketing Terhadap Minat Beli Konsumen Sari Ater Hotel & Resort Kabupaten Subang. Metode yang digunakan adalah metode survey dan teknik penarikan sampel adalah non probability sampling. Jenis penelitian ini adalah verifikatif kuantitatif. Responden dalam penelitian ini adalah konsumen Sari Ater Hotel & Resort Kabupaten Subang. Sampel yang diambil adalah 100 orang responden. Metode analisis data yang digunakan adalah analisis koefisien korelasi yang bertujuan untuk mengetahui besarnya pengaruh Digital Instagram Marketing sebagai variabel independen dengan Minat Beli Konsumen sebagai variabel dependen. Hasil penelitian ini menunjukan adanya pengaruh Digital Instagram Marketing yang berpengaruh signifikan terhadap Minat Beli Konsumen, dengan koefisien korelasi menunjukan terdapat hubungan yang sangat kuat antara Digital Instagram Marketing dengan Minat Beli Konsumen. Koefisien determinan menunjukan bahwa Digital Instagran Marketing Berpengaruh terhadap Minat Beli Konsumen Akan Jasa menginap pada Sari Ater Hotel & Resort Kabupaten subang.